Denying the Divinity of Christ and Proving the Prophethood of Muhammad in the Context of Comparative Religions: The Debate as a Model (Islamic Sciences Journal, 2023)
ABSTRACT                     Muslim academics have been familiar with theological and scientific debates from the early ages. Islam's academics and the members of the Ahl-AlKitab engaged in theological debates throughout the religion's history, touching on a wide range of topics related to worship, belief, dogma and more. The most prominent of these was their assertion that Jesus is God while also rejecting that Jesus preached the message of Muhammad. The verses in the Holy Qur'an, as well as the distorted bible, were evidence against them. These Muslim academics debunked the Christians' claims that Jesus is divine. They invalidated the Christian academics and provided evidence for what had been surmised from corrupted biblical accounts: that Jesus was informed of Muhammad's message and purpose.
Keywords: the divinity of Christ, the Annunciation, the distorted gospels, comparison of religions, debate.